2001
DOI: 10.1159/000046812
|View full text |Cite
|
Sign up to set email alerts
|

Functional Recovery of Hearing following AMPA-Induced Reversible Disruption of Hair Cell Afferent Synapses in the Avian Inner Ear

Abstract: Hair cells in the avian inner ear can regenerate after acoustic trauma or ototoxic insult, and significant functional recovery from hearing loss occurs. However, small residual deficits remain, possibly as a result of incomplete reestablishment of the hair cell neural synaptic contacts. The aim of the present study was to determine if intracochlear application of α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA), an excitotoxic glutamate agonist, causes reversible disruption of hair cell neural cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…Reng et al [11] showed that AMPA induced reversible hearing impairment in the avian ear. Similar findings were noted by Le Prell et al [12], who mentioned that the hearing deficit caused by chronic application of AMPA recovered within several days after cessation of the application.…”
Section: Discussionmentioning
confidence: 99%
“…Reng et al [11] showed that AMPA induced reversible hearing impairment in the avian ear. Similar findings were noted by Le Prell et al [12], who mentioned that the hearing deficit caused by chronic application of AMPA recovered within several days after cessation of the application.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of GluR2 expression would thus limit Ca 2+ entry and its deleterious consequences (Pellegrini‐Giampietro et al ., 1997; Feldmeyer et al ., 1999; Oguro et al ., 1999; Van Damme et al ., 2002; Friedman et al ., 2003), in particular in view of the high transmission rates in primary auditory neurons necessary for coding of the temporal information contained in sounds (Trussell, 1997). Interestingly, excitotoxicity in the adult cochlea does not result in massive primary auditory neuron death (Puel et al ., 1995, 1998; Zheng et al ., 1997; Reng et al ., 2001).…”
Section: Correlation With Developmental Eventsmentioning
confidence: 99%
“…The discovery that hair cells of the avian basilar papilla (BP), the functional equivalent of the mammalian organ of Corti, are regenerated after preexisting hair cells have been destroyed (Corwin and Cotanche 1988;Ryals and Rubel 1988;Warchol and Corwin 1996) has stimulated much interest in the possibility of hair cell regeneration therapy in mammals (Staecker and Van De Water 1998). The continuous formation of cochlear sensory epithelial cells with and without insult to the auditory system has also been demonstrated in the lower vertebrate inner ear, but not in mammals (Cotanche and Lee 1994;Stone and Rubel 2000;Reng et al 2001).…”
Section: Introductionmentioning
confidence: 99%